Peranan Kepemimpinan Dosen Dalam Membentuk Mahasiswa Berkarakter Di Perguruan Tinggi STIA Bagasasi Bandung - Danang Nugroho; Ade Cahyadi; Devi Tresna Rahayu; Farhadt Ripan Maulana; Kristin Nurhayati; Laila Juariyah (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
This research aims to delve into the role of lecturer leadership in shaping students' character at STIA Bagasasi College in Bandung. In the context of higher education, the role of lecturer leadership is crucial in guiding, inspiring, and setting a good example for students. A literature review approach is employed to elucidate this important role. From the analysis, it is found that lecturers serve as role models, mentors, learning facilitators, and developers of student skills. Lecturers who demonstrate integrity, professionalism, and dedication positively influence the character and behavior of students. Lecturer leadership also aids in creating a conducive learning environment and motivating students to achieve their maximum potential. Colleges need to support effective lecturer leadership through lecturer training, professional development, and fostering good relationships between lecturers and students. Thus, lecturer leadership plays a significant role in shaping the character and personal development of students at STIA Bagasasi College in Bandung.